2022
DOI: 10.3390/aerospace9090497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mass and Aerodynamic Efficiency of a High Aspect Ratio Wing for Prospective Passenger Aircraft

Abstract: The application of the wings with a high aspect ratio for future-oriented transport category aircraft is being considered. Such a solution makes it possible to increase fuel efficiency by reducing induced drag. This goal is achieved by increasing the wingspan, when the wings made of composite materials are used. The wings of an increased span complicate the arrangement of the aircraft in the existing infrastructure of airports. To eliminate this drawback, the application of folding wingtips was considered. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The weight of a passenger aircraft wing is approximately 8-12% of the aircraft structural weight and 30-40% of the airframe weight [4,[15][16][17]. Up to 30-40% of the structural weight is the weight of the skin.…”
Section: Aircraft Wing Specificsmentioning
confidence: 99%
See 3 more Smart Citations
“…The weight of a passenger aircraft wing is approximately 8-12% of the aircraft structural weight and 30-40% of the airframe weight [4,[15][16][17]. Up to 30-40% of the structural weight is the weight of the skin.…”
Section: Aircraft Wing Specificsmentioning
confidence: 99%
“…The aerodynamic drag of a wing can be up to 60% of the total drag of an aircraft [4,15,18]. This is due to many aspects such as profile drag, friction, and induced drag.…”
Section: Aircraft Wing Specificsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the challenges from the aircraft design perspective is to implement the capability to correctly predict the sensitivity with respect to the design variables described above, taking into consideration that most of the calculations are based on approximated formulas based on statistical estimations. In [26], an interesting study is reported that corrects the approximated formulas commonly used during the conceptual design phase that are able to estimate the sensitivity of the design point due to the variations in MTOW, aspect ratio and use of composites. In particular, a revised formula to estimate the structural weight has been proposed.…”
Section: Introductionmentioning
confidence: 99%